Hyperspectral Imaging A Perspective on Recent Advances and Applications - Huang, Jung Y. (IntechOpen, 2023)
Preprocessing Hyperspectral Imaging data and objectively retrieving meaningful information from high-dimensional data cubes present a number of challenging issues. This book offers a glimpse of the status of machine- and deep-learning methodological development, seeking to meet the challenge of new hyperspectral imaging applications.